ECONOMIC THRESHOLD LEVEL (ETL) OF STEM GIRDLER (OBEREOPSIS BREVIS) Swedenbord IN SOYBEAN - and R. JAGADEESHWAR, KANJARLA RAJASHEKAR, J. SATYANARAYANA, T. UMAMAHESHWARI (The Journal of Research, PJTSAU, 2021)
Stem girdler, Obereopsis brevis Swedenbord is a major pest of soybean in Telangana. Indiscriminate insecticidal application for management of this pest from seedling to harvesting stage has resulted in increased pesticidal residues in soybean. Studies on management of the pest based on economic threshold level (ETL) carried out during 2017 and 2018 revealed that three sprayings with triazophos @ 1.5 ml l-1 effectively managed stem girdler, O. brevis in soybean. More than three sprayings i.e., four and five sprayings though reduced the pest incidence to five percent and absolute zero respectively but were not cost economical and didnot increase the yield significantly. Three sprayings with triazophos at 10 percent incidence was on par with the recommendations of University (PJTSAU) and it was concluded that 10 percent damage can be treated as economic threshold level for stem girdler, O.brevis in soybean.